Response of Wheat Storage Proteins and Breadmaking Quality to Dimethylpyrazole-Based Nitrification Inhibitors under Different Nitrogen Fertilization Splitting Strategies - Ximena Huérfano; José-María Estavillo; Miren K. Duñabeitia; María-Begoña González-Moro; Carmen González-Murua; Teresa Fuertes-Mendizábal (Plants, 2021)
Improving fertilizer nitrogen (N) use efficiency is essential to increase crop productivity and avoid environmental damage. This study was conducted during four crop cycles of winter wheat under humid Mediterranean conditions (Araba, northern Spain). The effects of N-fertilization splitting and the application of the nitrification inhibitors (NIs) 3,4-dimethylpyrazole phosphate (DMPP) and 2-(3,4-dimethyl-1H-pyrazol-1-yl) succinic acid isomeric mixture (DMPSA) as strategies to improve grain quality were examined. The hypothesis of this study was to test if the partial ammonium nutrition and the reduction of fertilizer losses presumably induced by the application of NIs can modify the grain gliadin and glutenin protein contents and the breadmaking quality (dough rheological properties). Among both NIs assayed, only DMPP showed a slight effect of decreasing the omega gliadin fraction, following splitting either two or three times, although this effect was dependent on the year and was not reflected in terms of dough extensibility. The slight decreases observed in grain quality in terms of dough strength and glutenin content induced by DMPP suggest that DMPSA is more promising in terms of maintaining grain quality. Nonetheless, these poor effects exerted by NI application on grain quality parameters did not lead to changes in the quality parameters defining the flour aptitudes for breadmaking.